Oceanography of Harmful Algal Blooms on the Ecuadorian Coast (1997–2017): Integrating Remote Sensing and Biological Data - Borbor-Cordova, Mercy J.; Torres, Gladys; Mantilla-Saltos, Gabriel; Casierra-Tomala, Ashley; Bermúdez, J. Rafael; Renteria, Willington; Bayot, Bonny (Frontiers in Marine Science, 2019)
Ocean climate drivers and phytoplankton life strategies interact in a complex dynamic to produce harmful algal blooms (HABs). This study aims to integrate historical biological data collected during “red tide” events along the Ecuadorian coast between 1997 and 2017 in relation to five ocean variables derived from satellite remote sensing data to explain the seasonal drivers of coastal processes associated with HABs dynamics. Seasonality of the occurrence of HABs was assessed in relation to oceanographic variables by applying multiple correspondence analysis (MCA) to the Ecuadorian central coast (Zone 1) and at the outer and inner Gulf of Guayaquil (Zone 2). Sixty-seven HABs events were registered between 1997 and 2017. From a total of 40 species of phytoplankton identified, 28 were identified as non-toxic and the remaining 12 are well known to produce toxins. Dinoflagellates were the taxonomic group most highly associated with potential HABs events along the entire Ecuadorian coast. HABs appear to be constrained by the Humboldt coastal upwelling, high precipitation, and associated coastal runoff, with higher biomass abundance in the Gulf of Guayaquil than in the central coast. Results from the MCA reveal that in the central Ecuadorian coast (oligotrophic system), toxic HABs occurred with low abundance of dinoflagellates, while in the Gulf of Guayaquil (eutrophic system), toxic HABs corresponded to a high abundance of dinoflagellates. In both cases, high values were found for sea surface temperature, precipitation, and irradiance—characteristic of wet seasons or El Niño years. Non-toxic HABs occurred with a high abundance of dinoflagellates, ciliates, and centric diatoms, corresponding to colder waters and low levels of precipitation and irradiance. These findings confirm that dinoflagellates display several strategies that enhance their productive capacity when ocean conditions are warmer, allowing them to produce toxins at high or at low concentrations. Considering that the Gulf of Guayaquil is essential to tourism, the shrimp industry, fisheries, and international shipping, these findings strongly suggest the need to establish an ecosystem health research program to monitor HABs and the development of a preventive policy for tourism and public health in Ecuador.